Soil carbon storage potential of acid soils of Colombia's Eastern High Plains - Hyman, Glenn; Castro, Aracely; Da Silva, Mayesse; Arango, Miguel; Bernal, Jaime; Pérez, Otoniel; Rao, Idupulapati Madhusudana (Frontiers in Sustainable Food Systems, 2022)
Improving soil organic carbon (SOC) storage enhances soil quality and mitigates climate change. Agricultural and livestock specialists increasingly view tropical grasslands as a target for storing more soil carbon while boosting productivity. Previous research in the 1990s showed the promise of improving soil SOC storage in the Eastern High Plains of Colombia. But these studies were limited to two experimental stations, without focusing on conditions on farms or under variable management. This research was aimed to test whether those early studies did indeed reflect possibilities for improving SOC storage and livestock productivity. We measured SOC stocks on farms throughout the study area and at one of the experiment stations from previous research in Colombia’s Eastern High Plains. We sampled other predominant land uses to map SOC storage across the nearly 1 million ha study area. We also constructed scenarios suggesting changes in SOC and productivity based on land-use changes. The high SOC accumulation found at experimental sites in the 1990s declined by 24 years later. However, SOC storage was more than 27 Mg ha-1 yr-1 higher than reference native savanna sites, with an accumulation rate of 0.96 Mg ha-1 yr-1. On farms under variable management, improved pastures stored 10 Mg ha-1 more SOC than degraded pastures or native savanna. We estimate that variable carbon storage observed across soils of the 1 million ha study area could store 0.08 Gt of carbon down to 1 m depth, with substantial variation across the region. While the SOC measured in the early 1990’s did not persist under inadequate management over the period of two decades, the potential to accumulate SOC in the soils of Colombia’s Eastern High Plains through appropriate land use and management is high, pointing to a sustainable livestock strategy that boosts productivity and reduces emissions.